Place meaning of the historic square as tourism attraction and community leisure space - Zakariya, Khalilah; Harun, Nor Zalina; Mansor, Mazlina (Elsevier, 2015)
Squares serve as an integral civic space in cities where historic events and socializing activities take place.Theyare an attraction for locals and tourists alike. However, some historic squares go through physical transformations to meet the demands of urban growth. This paper compares the place meaning that locals and tourists ascribetoDataranPahlawan, a historic urban square in Melaka that was redeveloped. Based on the results that reveal the shift in meanings among these different visitors, this paper recommends that efforts need to be taken to instil conservation awareness on the values of historic squares to cities to accommodate the needs of locals and tourists.